"I felt a bit daunted, I've never written a song before": cancer patients' experiences of original songwriting. Issue 1 (1st June 2016) - O'brien, Emma; Grocke, Denise; Dileo, Cheryl
Abstract : Background : GOLM – Guided Original Lyrics and Music is a specialised songwriting protocol that follows a series of stages to create an original song with the participant. The song is newly composed with original lyrics and original music. The method is under-pinned by the therapeutic intent of ensuring that the participant is involved in every step of the song's creation. Objective : Nine participants were interviewed about their experience of songwriting using GOLM as part of a larger multi-site waitlisted randomised controlled trial with the overarching research question "What is the effect of GOLM on adult cancer patients' quality of life, mood, distress levels and satisfaction with hospital stay; and how is songwriting experienced?" Method : The participants' experience was explored in qualitative interviews; 15 composite themes emerged and a global essence of the "lived experience". Conclusion : The lived experience of writing an original song in music therapy using the therapeutic songwriting method GOLM was "a dynamic process across an emotional continuum, with challenging aspects of trepidation and excitement, and consequent rewards of feelings of pride and happiness."